An elusive record exposed: radiocarbon chronology of late Holocene human settlement in the northern Congo Basin, southern Central African Republic. Issue 2 (3rd April 2018) - Lupo, Karen D.; Kiahtipes, Christopher A.; Schmitt, Dave N.; Ndanga, Jean-Paul; Craig Young, D.; Simiti, Bernard
ABSTRACT: Archaeological surveys and excavations in the NGotto Forest Reserve, Central African Republic, discovered 98 artefact concentrations or cultural features that included ceramic scatters, iron-ore mines and iron smelting features. These investigations provide, for the first time, a series of radiocarbon dates that chronicle the timing and context of prehistoric occupation along the northern margin of the Congo Basin rain forest in the Central African Republic. Thirty-three age estimates from 19 sites are distributed throughout the late Holocene and together document 2500 years of occupations. A number of the dates are from iron extraction and processing features that reflect extensive pre-colonial use of the area between about AD 1750 and 1840, while a radiocarbon date of 2179 ± 37 BP in direct association with pottery signals settlement by ceramic-bearing peoples perhaps as early as 350 cal. BC. Three radiocarbon dates from two sites reflect occupations during the purported hiatus and reduction in regional forest populations c. 1400-800 BP and five dates from four additional sites in southern Central African Republic rain forests also fall during this interval. In concert with scrutiny of summed probability distributions and potential artefacts embedded within the radiocarbon calibration curve, the number of these dates question the reality of this occupational hiatus, at least in the north-central Congo Basin.